2014
DOI: 10.1080/09585192.2014.962563
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management, Lean processes and outcomes for employees: towards a research agenda

Abstract: Lean management or lean thinking is a process improvement technique that along with Six Sigma is used in an increasing range of workplaces. This special issue focuses on the use of Lean in developed countries. This increased usage reflects a growing propensity for managers to launch initiatives to upgrade the efficiency and productivity of the enterprises that they manage, usually in an attempt to enhance the cost-effectiveness of operations. This special issue of the IJHRM includes eight articles in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 27 publications
2
62
0
2
Order By: Relevance
“…In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation. This research is also congruent with the study of Bamber et al (2014), Albliwi et al (2014) and Tanik and Sen (2012) whose conclusions about the significant impact of culture, educational level and knowledge of statistics on the success of Six Sigma projects is seen as equally important in German SMEs. Although the study presented here only considered seven SMEs within the German manufacturing supply chain it has addressed to some extent the research gap (Atmaca and Girenes, 2013;Thomas and Barton, 2006) of human behavioural factors and their relationship with LSS.…”
Section: Research and Practical Implicationssupporting
confidence: 78%
See 2 more Smart Citations
“…In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation. This research is also congruent with the study of Bamber et al (2014), Albliwi et al (2014) and Tanik and Sen (2012) whose conclusions about the significant impact of culture, educational level and knowledge of statistics on the success of Six Sigma projects is seen as equally important in German SMEs. Although the study presented here only considered seven SMEs within the German manufacturing supply chain it has addressed to some extent the research gap (Atmaca and Girenes, 2013;Thomas and Barton, 2006) of human behavioural factors and their relationship with LSS.…”
Section: Research and Practical Implicationssupporting
confidence: 78%
“…The result of this research is also consistent with the studies undertaken by Kanpp (2015), Lam et al (2015), Antony (2014), Bamber et al (2014), Stanton et al (2014), Zu et al (2010), Calvo-Mora et al (2014), Laohavichien et al( 2011), andBaird et al (2011) who argue that organisational culture and behavioural factors are key enablers for any TQM practice including LSS. This study has found a strong relationship between organisational culture and readiness to implement LSS in German manufacturing SMEs.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Bamber [5]et al continue the topic of lean practices, but their study is based on the theory of human research management. They identify the relations between lean management, human resource management and employee efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Bamber et al [5] analyze the established literature on how different industries cut costs, improve quality and increase overall efficiency in recent decades. The review shows the main process improvement techniques; there are lean tools among them, namely Toyota Production System and Six Sigma.…”
Section: Introductionmentioning
confidence: 99%